Artificial Neural Network vs. Support Vector Machine For Speech Emotion Recognition - Mohamed. A. Ahmad (Tikrit Journal of Pure Science, 2023)
Today, the subject of emotion recognition from speech got the attention of many researchers who are interested in the topic of speech recognition and it has engaged in many applications. Furthermore, Speech Emotion Recognition (SER) a pivotal part of influential human interaction and it has been a modern challenge to speech processing. SER has two basic phases; which are, features extraction and emotion classification. This paper presents a comparison in performances of two popular techniques used for classification that Artificial Neural Network (ANN) as well as Support Vector Machine (SVM). Furthermore, gives a view on the collection of corpus, feature extraction techniques and classification methods, which are regarding to emotion detection from wave speech signal.